2008
DOI: 10.1159/000151448
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of Two Novel <i>PAX9</i> Mutations

Abstract: The paired-domain transcription factor PAX9 plays a critical role in tooth development, as heterozygous mutations in PAX9 have been shown to be associated with human tooth agenesis. In this study, we report 2 novel missense mutations, gly6arg (G6R) and ser43lys (S43K), in the paired domain of PAX9 in Chinese patients with varying degrees of nonsyndromic tooth agenesis. Excluding third molars, the individual with the G6R mutation was missing 2 mandibular incisors and a maxillary premolar, while the phenotype of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 46 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…No MSX1 mutation could be identified, but a PAX9 missense mutation substituting isoleucine for a highly conserved phenylalanine (p.Phe15Ile) was identified in the paired box domain crucial for DNA binding. Wang et al identified a PAX9 mutation (p.Gly6Arg) causing a mild hypodontia phenotype almost identical to that of our proband’s mother [19]. Interestingly, our p.Phe15Ile substitution is structurally close to the p.Gly6Arg mutation.…”
Section: Discussionsupporting
confidence: 62%
“…No MSX1 mutation could be identified, but a PAX9 missense mutation substituting isoleucine for a highly conserved phenylalanine (p.Phe15Ile) was identified in the paired box domain crucial for DNA binding. Wang et al identified a PAX9 mutation (p.Gly6Arg) causing a mild hypodontia phenotype almost identical to that of our proband’s mother [19]. Interestingly, our p.Phe15Ile substitution is structurally close to the p.Gly6Arg mutation.…”
Section: Discussionsupporting
confidence: 62%
“…Another in vitro study using the PAX9 protein comprising a mutated paired domain with amino acid change Arg28Pro revealed dramatically reduced ability to form protein‐DNA complex . Wang et al made functional analysis on Gly6Arg and Ser43Lys substitutions and reported no effect on nuclear localization of PAX9 but found reduced DNA‐binding activity of the mutant protein compared to the wild type. These findings were provided with additional support by observations of Zhao et al who studied Arg47Trp amino acid change.…”
Section: Mutations and Polymorphisms In The Pax9 Genementioning
confidence: 99%
“…individuals with hypodontia were mandibular second premolars, followed by maxillary lateral incisors, as reported in a recent meta-analysis, 33 it is likely that there is an overlapping phenotype in some of the individuals with WNT10A and WNT10B mutations. The selective pattern in WNT10B mutants is also different from that of mutations in other oligodontia-associated genes, such as MSX1 (missing second premolar) and PAX9 (agenesis of molars), as described previously 7,10,11,34 and currently in the individuals with the p.Ile97Leufs*217 variant ( Figure S1). Regardless, protein-protein-interaction and genetic studies have shown crosstalk between PAX9 and the Wnt pathway (e.g., AXIN2) or MSX1 in dental tissues, 11 which are essential for the establishment of the odontogenic potential of the mesenchyme.…”
mentioning
confidence: 68%
“…5 By Sanger sequencing of these oligodontia-associated genes, we have previously identified mutations in most of these genes in Chinese individuals with non-syndromic oligodontia. [6][7][8][9][10] However, no mutations were detected in nearly half of the examined affected individuals, suggesting the existence of unidentified genetic etiologies. Presumably, additional crucial components in several defined canonical pathways (such as BMP, FGF, NF-kB, P53, PAX, and Wnt, which involve tooth development) could be the candidates.…”
mentioning
confidence: 99%